Análise da interação externa para a inovação nas empresas de TIC na cidade de Curitiba - Uemura, Marcelo Takashi (2019)
Innovation is one of the essential elements for the survival and competitiveness of organizations. In order to quantify innovation management practices, FIEP (Federação das Indústrias do Paraná) conducted a survey called Bússola da Inovação, on indicators that measure the degree of innovation carried out by sectors and cities. There are ten indicators called innovation dimensions, including: Results of Innovation, Fundraising, Investments, Innovation Activities, External Interaction, Methods of Protection, Internal Environment, Research and Development, Information and Knowledge and Innovation Management. This research had as main objective to identify the main barriers for external interactions in the innovation processes of Information and Communication Technology companies in the city of Curitiba, due to the low score in the dimension "External Interaction" obtained by the Bússola da Inovação. In terms of specific objectives, the elements used to measure the "External Interaction" dimension by the Bússola da Inovação were identified, identified the theoretical barriers of external interaction for innovation and analyzed their relevance in information and communication technology companies. As a methodology, the research was characterized as qualitative, descriptive and exploratory, with the collection of data through semistructured interviews with companies selected among the respondents of the Bússola da Inovação in the Information Technology sector in Curitiba. These data were transcribed and used with the support of the Atlas.ti tool for a content analysis, identifying the relevant points of the interviewees' speeches, emphasizing the difficulties in the interactions with external actors with the purpose of innovating. The results showed consistency with the indicators presented by the Bússola da Inovação, with clients and consumers as the main element of external interaction, as well as difficulties with other actors with lower innovative interactive performance. The main barriers identified in the results of this research were the lack of partners for innovation, lack of focus for external interaction, especially with professional training centers, government agencies, regulatory organizations, specialized innovation support institutions and surrounding communities. Other external actors presented interaction of a more moderate level, being quite punctual in the perspective of some companies interviewed. A relevant aspect was the lack of understanding about who some of the actors were questioned, which may have reflected in the quantitative result of the Bússola da Inovação.